Best practices and tools for creating WebSphere Commerce sites - Cunico, Hernan; Nielsen, Nicolai; Sharma, Sanjeev (Information technology executive) (IBM redbooks., 2005)
This IBM Redbooks publication is an update to the IBM Redpaper Best Practices and Tools for Creating IBM WebSphere Commerce Sites, REDP-3616. It introduces a systematic project development method that was specifically adapted for the creation of e-commerce sites using the WebSphere Commerce family of software products. This book provides examples on the best practices for developing new sites or migrating existing ones. The objective is to document how the tools can be combined with the systematic development method to streamline a WebSphere Commerce project.